Biosimilars in Europe - Vulto, Arnold G.; Simoens, Steven; Huys, Isabelle (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint examines regulatory, pricing and reimbursement issues related to the market access and uptake of off-patent biologics, biosimilars, next-generation biologics and competing innovative medicines in European countries.